STUDY OF INCOME AND CHARACTERISTICS OF CERTIFIED RICE SEED CAPTURE BUSINESS IN BENGKULU TENGAH DISTRICT AND ITS SUSTAINABILITY - Feriady, Anton; Mulyadi, Maheran; Mutmainnah, Elni (Jurnal AGRISEP, 2022)
This study aims to examine the income and characteristics of certified rice seed breeding businesses in Central Bengkulu Regency which has a recommendation as a certified rice seed breeder from the BPSB (Seed Monitoring and Certification Center) Office of Horticulture and Plantation Food Crops Bengkulu Province.The data analysis method used in this research is using a mix method, namely the combination of quantitative and qualitative which is carried out simultaneously.The results showed that the breeding business of certified rice seeds in Bengkulu Tengah Regency was profitable, amounting to Rp. 23,719,248/planting season and based on the study of its characteristics it was necessary to improve and evaluate the role of the Seed, Plant Supervisor as a supervisor to the mentoring role seeing farmers who cultivate certified seeds in Central Bengkulu Regency has the characteristics of being male, with the highest average age being above 63 years, with an average land tenure of 0.5 to 1 hectare with the status of own land and having a number of dependents. mostly between 3 to 4 people. It is recommended to strengthen the capacity of captive farmers who do not continue through a selection process based on: age, gender, education, number of dependents, and land area owned. as well as improving the skills and knowledge of breeder farmers regarding certified rice seeds and their business prospects.